Junction of the redox dynamic, orchestra of signaling, and altered metabolism in regulation of T- cell lymphoma - Singh, Shantanu; Maurya, Akhilendra Kumar (Frontiers in Oncology, 2023)
T-cell lymphoma is a hematologic neoplasm derived from the lymphoid lineage. It belongs to a diverse group of malignant disorders, mostly affecting the young population worldwide, that vary with respect to molecular features as well as genetic and clinical complexities. Cancer cells rewire the cellular metabolism, persuading it to meet new demands of growth and proliferation. Furthermore, the metabolic alterations and heterogeneity are aberrantly driven in cancer by a combination of genetic and non-genetic factors, including the tumor microenvironment. New insight into cancer metabolism highlights the importance of nutrient supply to tumor development and therapeutic responses. Importantly, oxidative stress due to an imbalance in the redox status of reactive species via exogenous and/or endogenous factors is closely related to multiple aspects of cancer. This alters the signaling pathways governed through the multiple intracellular signal transduction and transcription factors, leading to tumor progression. These oncogenic signaling molecules are regulated through different redox sensors, including nuclear factor-erythroid 2 related factor 2 (Nrf2), phase-II antioxidant enzyme, and NQO1 (NADPH quinone oxidoreductase (1). The existing understanding of the molecular mechanisms of T-cell lymphoma regulation through the cross-talk of redox sensors under the influence of metabolic vulnerability is not well explored. This review highlights the role of the redox dynamics, orchestra of signaling, and genetic regulation involved in T-cell lymphoma progression in addition to the challenges to their etiology, treatment, and clinical response in light of recent updates.